Economic Efficacy Assessment of Deteriorating Protection Structures Subjected to Natural Phenomena in Mountains - Chahrour, Nour; Bérenguer, Christophe; ICASP14; Tacnet, Jean-Marc (My University, 2023)
Natural phenomena in mountains (e.g., torrential floods, debris flows) pose threat to people and material assets (e.g., houses, roads). Depending on their intensity, they can result in direct damages (e.g., destruction) and/or indirect damages (e.g., infrastructure disruption). The overall impact of a natural phenomenon can be expressed as the sum of all economic losses. Different types of protection structures are implemented in mountains aiming to resist natural phenomena and therefore to protect vulnerable exposed elements. However, these structures deteriorate over time due to the high-intensity phenomena they are subjected to. If not regularly maintained, the level of protection provided by these structures will be reduced. Assessing the dynamic efficacy of protection structures corresponds to evaluating the level of protection they provide and therefore the reduction in the level of risk. Recent studies have focused on developing stochastic approaches that make it possible to model and understand the physics behind the deterioration process of protection structures when subjected to natural phenomena over their lifetime. The main objectives behind these approaches were to assess the technical efficacy (structural, functional) of protection structures and to support their maintenance decision-making. Nonetheless, none of these research studies has considered the economic efficacy of these structures, which is related to risk assessment. To be economically effective, there should be a balance between the level of protection provided by protection structures to downstream elements at risk and the expenses spent on them, as done in classical cost-benefit analysis. Therefore, the economic efficacy can be assessed by comparing the total cost of applied interventions (inspection, maintenance, construction) spent on the structures with the economic losses (people, houses, infrastructures) resulting from natural phenomena. To carry out this assessment, risk analysis should be first performed. This study aims in proposing a conceptual model that assesses the risk level induced by natural phenomena in mountains while considering different deterioration levels of protection structures and different maintenance strategies. This requires performing hazard (probability) and vulnerability (consequences) analysis. It supports cost-benefit analysis, which is adopted to assess the economic efficacy of protection structures. Finally, a simple numerical application is carried out to clarify the proposed model.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED